Transfemoral versus transcarotid access for transcatheter aortic valve replacement - Olivier Maud-Emmanuelle; Di Cesare Alessandro; Poncet Anne; Brasselet Camille; Metz Damien; Biancari Fausto; Ruggieri Vito Giovanni; The Reims Heart Team Group (Elsevier Inc., 2022)
Objectives: To compare the outcomes after transcatheter aortic valve replacement (TAVR) through a transfemoral (TF) and transcarotid (TC) access at our institution.
Methods: From January 2014 to January 2020, 62 TC-TAVR and 449 TF-TAVR were performed using 2 prosthesis devices (Edwards SAPIEN 3, n = 369; Medtronic Evolut R, n = 142). Propensity score matching was used to adjust for imbalance in the baseline characteristics of the study groups.
Results: Propensity score matching provided 62 matched pairs with comparable operative risk (mean European System for Cardiac Operative Risk Evaluation II, TC-TAVR 7.6% vs TF-TAVR 6.6%, P = .17). Thirty-day mortality (4.8% vs 3.2%, P = 1.00) and 2-year mortality (11.3% vs 12.9%, P = .64) after TC-TAVR were comparable with TF-TAVR. Strokes were numerically more frequent after TC-TAVR compared with TF-TAVR (3.2% vs 0%, P = .23), but the difference did not reach statistical significance. TF-TAVR was associated with a significantly greater risk of permanent pacemaker implantation (29.0% vs 12.9%, P = .04) compared with TC-TAVR. Other complications were not frequent and were similarly distributed between the matched groups.
Conclusions: TC access for TAVR was associated with satisfactory results compared to the femoral access. TC-TAVR could be considered a valid and safe alternative to TF-TAVR when femoral access is contraindicated. © 2022